Barriers facing Bangladeshi Adolescents in Learning about Sexual and Reproductive Health - Kamruzzaman Kamruzzaman; Sajal Roy; Ashish Kumar Singh (UIN Sunan Gunung Djati, 2022)
This paper looks into the barriers faced by Bangladeshi adolescents in learning about sexual and reproductive health. A mixed method approach was used to generate data gathered from the two study sites named Dhormasor Mohisa Trimukhi Uchho Bidalay and the Jaforgonj High School located in the Rangpur district, the northern part of Bangladesh. Thematic analysis was employed to develop themes, priori and other memos. Our findings demonstrate several key issues, all of which negatively impact adolescent Sexual Reproductive Health (SRHR) education. First, there is the lack of teacher training and experience in SRHR class lectures, as well as parental ignorance. Second, there are social stigmas, social taboos and cultural rigidity. Third, there are significant institutional barriers like the lack of textbook information, combined classes and age discrepancies between teachers and students. Fourth, male teachers often giveÂ Â SRHR lectures to female students, and female teachers give SRHR lectures to males. Fifth, misuse of appropriate technology and sometimes its lack of access can also prevent adolescents obtaining correct information about SRHR. This study contributes to the field of gender and public health.